Analisis Perbedaan Tingkat Representasi pada Topik Interferensi dengan Berbantuan Virtual Lab Phet dalam Uji Pola Gelap Terang - Nazwa, Myfa; Hasanah, Nurul; Gunawan, Rifa Ardhana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to deepen students' understanding of the concept of light interference by using the PhET Virtual Lab simulation as an interactive learning medium. The research subjects consisted of five students from the physics education study program who were chosen deliberately. The research method used is a descriptive experimental design, which involves stages of simulation, measurement, calculation validation, and concept understanding tests. The results showed a clear relationship between the distance between the gaps and the light pattern on the screen, which is in accordance with the theory of light interference. The PhET simulation was proven to be able to increase students' comprehension scores, which were initially only 40% on the pre-test, to 81.6% on the post-test. The visualization provided by simulations helps students to better understand the relationship between theory and phenomena in more depth. This simulation also allows students to practice concepts through various representations, such as verbal, graphic and mathematical. This research recommends the use of the PhET Virtual Lab simulation as an effective learning medium to increase understanding of physics concepts, especially regarding light interference.